ETNOBOTANI TUMBUHAN OBAT DI DESA NIFUKANI KABUPATEN TIMOR TENGAH SELATAN - Riska Talan; Andam Suriaty Ardan; Arini Rahma Dhani; Mario J Santrum (SINERGI : Jurnal Riset Ilmiah, 2026)
Research on the Ethnobotany of Medicinal Plants in Nifukani Village, South Central Timor Regency aims to identify the ethnobotany of medicinal plants in Nifukani Village, South Central Timor Regency. This research was conducted in March 2025 in Nifukani Village, South Central Timor Regency. This study is a qualitative descriptive research, using data collection techniques such as interviews or verbal accounts from traditional community leaders and field surveys to obtain specimens and documentation of plant specimens. The results of ethnobotanical research on medicinal plants in Nifukani Village, South East Timor Regency, found 25 types of medicinal plants belonging to 18 families that are used as medicine. The methods of processing plants as medicine include boiling, grating, pounding, chewing, burning, and eating them directly. The diseases that can be treated are: wounds, bloating, tinea versicolor, stomach problems, malaria, high fever, tumors, breast cancer, improving blood circulation, internal heat, diarrhea, detoxifying poison, worm infections, gomag/melepu in babies' mouths, boils, cough, poisoning, eye pain, vaginal discharge, cold allergies, stroke, low blood pressure, scabies, abdominal pain, kidney stones, chickenpox, cough, jaundice, burns, and internal wounds. The results of this study indicate that the Balus Permai Village community has deep and broad ethnobotanical knowledge about medicinal plants. Evidently in this study there were 20 plant species from 15 families used by the community in medicine and each plant has a different processing method. Some dominant plants that are often used include Wunis, Lia, Welu, Bangkabu, Legi, Tongkak, Binahong. Knowledge about the use of medicinal plants is generally passed down orally from generation to generation, so it can be concluded that the Balus Permai Village community has rich and hereditary ethnobotanical knowledge about the use of medicinal plants for various diseases.